2016
DOI: 10.1002/etc.3374
|View full text |Cite
|
Sign up to set email alerts
|

Germination and early plant development of ten plant species exposed to titanium dioxide and cerium oxide nanoparticles

Abstract: Ten agronomic plant species were exposed to different concentrations of nano-titanium dioxide (nTiO2 ) or nano-cerium oxide (nCeO2 ) (0 μg/mL, 250 μg/mL, 500 μg/mL, and 1000 μg/mL) to examine potential effects on germination and early seedling development. The authors modified a standard test protocol developed for soluble chemicals (OPPTS 850.4200) to determine if such an approach might be useful for screening engineered nanomaterials (ENMs) and whether there were differences in response across a range of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(49 citation statements)
references
References 29 publications
4
33
0
1
Order By: Relevance
“…It has been reported previously (Lopez-Moreno et al, 2010b) that root growth was reduced in alfalfa and tomato but was significantly promoted in cucumber and corn. Andersen et al (2016) found that nanoceria alter average root length, and hence root growth was decreased in cabbage and corn, but was promoted in cucumber and onion. Ma et al (2010) only detected a reduction on the root elongation in lettuce but no effect was detected for a suspension of 2000 mg L -1 nanoceria for rape, radish, wheat, cabbage, tomato, and cucumber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported previously (Lopez-Moreno et al, 2010b) that root growth was reduced in alfalfa and tomato but was significantly promoted in cucumber and corn. Andersen et al (2016) found that nanoceria alter average root length, and hence root growth was decreased in cabbage and corn, but was promoted in cucumber and onion. Ma et al (2010) only detected a reduction on the root elongation in lettuce but no effect was detected for a suspension of 2000 mg L -1 nanoceria for rape, radish, wheat, cabbage, tomato, and cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the differences among angiosperms and ferns, some authors (Lopez-Moreno et al, 2010b) showed, at concentrations of nanoceria from 500 to 2000 mg L -1 , relatively low to moderate toxicity on seed germination of alfalfa (Medicago sativa), cucumber (Cucumis sativa), tomato (Solanum lycopersicum) and corn (Zea mays). Nanoceria did not affect germination in lettuce (Lactuca sativa), tomato (Solanum lycopersicum), cabbage (Brassica oleracea), soybean (Glycine max), carrot (Daucus carota), perennial ryegrass (Lolium perenne), corn (Zea mays), cucumber (Cucumis sativus), oat (Avena sativa), and onion (Allium cepa) at concentrations between 250 and 1000 mg L -1 (Andersen et al, 2016). The toxic effect at the highest concentration tested (3000 mg L -1 ) was more marked for nanoceria than for bulk-CeO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…(Szymanska et al, 2016), cabbage (Andersen et al, 2016), oilseed rape or canola ( Brassica napus L.) (Mahmoodzadeh et al, 2013), corn (Andersen et al, 2016), cucumber (Servin et al, 2012), fennel ( Foeniculum vulgare Mill.) (Feizi et al, 2013), lettuce ( Lactuca sativa L.) (Andersen et al, 2016), oat ( Avena sativa L.) (Andersen et al, 2016), onion ( Allium cepa L.) (Haghighi and Teixeira da Silva, 2014), parsley ( Petroselinum crispum Mill.) (Dehkourdi and Mosavi, 2013), red clover ( Trifolium pretense L.) (Gogos et al, 2016), soybean ( Glycine max Merr.)…”
Section: Ti Improves Plant Performancementioning
confidence: 99%
“…The results of the interaction effect among the three Solanaceae crops and nanomaterials levels, herein, revealed that low and high levels of ZnO and TiO 2 nanomaterials (50 and 150 mg/L) in the two successive seasons recorded lower growth criteria compared to 100 mg/L, but generally higher than hydro-primed seedlings. The seeds primed with TiO 2 nanoparticles enhanced germination rates, promoted root lengths as well as improved seedling growth (Andersen et al, 2016;Szymanska et al, 2016). On the other hand, the promoter impact of nanoscale ZnO may be associated with Zn's activity as a precursor in the formation of auxins that increase elongation and cell division (Teale et al, 2006), thus higher transplants lengths.…”
Section: Seedlings Growth Characters As Affected By the Metal Oxide Nmentioning
confidence: 99%